Real-time three-dimensional echocardiography: technological gadget or clinical tool? - Badano, L; Dall'Armellina, E; Monaghan, M; Pepi, M; Baldassi, M; Cinello, M; Fioretti, P (2007)
The complex anatomy of cardiac structures requires three-dimensional spatial orientation of images for a better understanding of structure and function, thereby improving image interpretation. Real-time three-dimensional echocardiography is a recently developed technique based on the design of an ultrasound transducer with a matrix array that rapidly acquires image data in a pyramidal volume. The simultaneous display of multiple tomographic images allows three-dimensional perspective and the anatomically correct examination of any structure within the volumetric image. As a consequence, it is less operator-dependent and hence more reproducible. Dedicated software systems and technologies are based on high-performance computers designed for graphic handling of three-dimensional images by providing possibilities beyond those obtainable with echocardiography. This methodology allows simultaneous display of multiple superimposed planes in an interactive manner as well as a quantitative assessment of cardiac volumes and ventricular mass in a three-dimensional format without a pre-established assumption of cardiac chamber geometry. In addition, myocardial contraction and/or perfusion abnormalities are clearly identified. Finally, real-time three-dimensional colour Doppler flow mapping enables complete visualisation of the regurgitant jet and new ways of assessing regurgitant lesion severity. Thus, this technique expands the abilities of non-invasive cardiology and may open new doors for the evaluation of cardiac diseases. In this article, current and future clinical applications of real-time three-dimensional echocardiography are reviewed.